Diseño e implementación de un banco didáctico de energía solar fotovoltaica para prácticas de los estudiantes de la Universidad Antonio Nariño sede Villavicencio (2021)
The depletion of conventional energy sources has led to promoting the application of renewable energies in different countries in order to reduce environmental problems and climate change. Specifically, this degree project provides an approach and direction in the use and application of photovoltaic solar energy through a didactic practice bank for students of the Antonio Nariño University, Villavicencio campus, through the study of preliminary concepts, analysis, selection of components. , design and manufacture of the bench and preparation of laboratory practice guides.